Identification of RegIV as a novel GLI1 target gene in human pancreatic cancer. - Feng Wang (PLoS ONE, 2011)
GLI1 is the key transcriptional factor in the Hedgehog signaling pathway in pancreatic cancer. RegIV is associated with regeneration, and cell growth, survival, adhesion and resistance to apoptosis. We aimed to study RegIV expression in pancreatic cancer and its relationship to GLI1.GLI1 and RegIV expression were evaluated in tumor tissue and adjacent normal tissues of pancreatic cancer patients and 5 pancreatic cancer cell lines by qRT-PCR, Western blot, and immunohistochemistry (IHC), and the correlation between them. The GLI1-shRNA lentiviral vector was constructed and transfected into PANC-1, and lentiviral vector containing the GLI1 expression sequence was constructed and transfected into BxPC-3. GLI1 and RegIV expression were evaluated by qRT-PCR and Western blot. Finally we demonstrated RegIV to be the target of GLI1 by chromatin immunoprecipitation (CHIP) and electrophoretic mobility shift assays (EMSA).The results of IHC and qRT-PCR showed that RegIV and GLI1 expression was higher in pancreatic cancer tissues versus adjacent normal tissues (p<0.001). RegIV expression correlated with GLI1 expression in these tissues (R = 0.795, p<0.0001). These results were verified for protein (R = 0.939, p = 0.018) and mRNA expression (R = 0.959, p = 0.011) in 5 pancreatic cancer cell lines. RegIV mRNA and protein expression was decreased (94.7±0.3%, 84.1±0.5%; respectively) when GLI1 was knocked down (82.1±3.2%, 76.7±2.2%; respectively) by the RNAi technique. GLI1 overexpression in mRNA and protein level (924.5±5.3%, 362.1±3.5%; respectively) induced RegIV overexpression (729.1±4.3%, 339.0±3.7%; respectively). Moreover, CHIP and EMSA assays showed GLI1 protein bound to RegIV promotor regions (GATCATCCA) in pancreatic cancer cells.GLI1 promotes RegIV transcription by binding to the RegIV gene promoter in pancreatic cancer.